Enhanced EAP-based pre-authentication for fast and secure inter-ASN handovers in mobile WiMAX networks - Nguyen, Thuy Ngoc (2013)
Mobile WiMAX is yet to meet the expectation from mobile users to provide secured and seamless services. Long delay in the time-consuming authentication procedure is a well-known bottleneck of the IEEE 802.16e handover scheme, causing service disruption when a mobile user moves between base stations. A pre-authentication-based handover scheme for mobile WiMAX networks aims to achieve fast and secure inter-ASN handovers. However, it is shown to be vulnerable to Denial of Service (DoS) and replay attacks. In this paper, we propose an Enhanced EAP-based pre-authentication (EEP) scheme to overcome the vulnerability of the above-mentioned scheme with much less requirements on the computation and communication resources.